The Simultaneous Vacancy of the Definitive Regent and Vice Regent Positions in Muara Enim and Ogan Komering Ulu - dedeng zawawi; Alip D Pratama; Hatta Azzuhri (Veteran Law Review, 2023)
The condition of a vacancy in the Head of the Region position in a problem that occurred in Muara Enim and Ogan Komering Ulu becomes a unique issue in filling the position because the vacancy happened simultaneously in both the Regent and Vice Regent positions. Currently, in Muara Enim, the position is filled by an Acting Regent (Plt) who was appointed by the Regional People's Representative Council (DPRD) after the Vice Regent's election. However, there is currently a legal challenge in the State Administrative Court (PTUN) regarding the DPRD's appointment decision. For Ogan Komering Ulu Regency, the elected Regent and Vice Regent from the 2020 local elections, Kuryana Azis, passed away shortly after being inaugurated as Regent. Meanwhile, the Vice Regent, who had previously been a corruption defendant, was unable to perform his duties one day after the inauguration. Currently, the Governor has appointed the Head of the Department as the Acting Regent. However, Article 65 paragraphs (5) and (6) of the Local Government Law state that the Secretary of the Region (Sekda) should be the one to carry out the duties as the Acting Regent. "This research aims to provide an answer on the appointment process of the Regent and Vice Regent positions that are vacant simultaneously. This is because the Local Government Law and the Regional Head Election Law only regulate the vacancy of one position, either the Regent or Vice Regent. The method used in this research is a juridical-normative approach, with a combination of legislation analysis, case studies, and comparative approaches. The results of this research show that the appointment of a Substitute Regional Head follows the provisions of Law No. 23 of 2014, Law No. 10 of 2016, and Government Regulation No. 12 of 2018. The position of the Regional Head, Acting Regional Head, Acting Regent, Interim Regent, and Acting Officer is regulated under Law No. 23 of 2014, Law No. 30 of 2014, Law No. 10 of 2016, Government Regulation No. 49 of 2008, and Government Regulation No. 1 of 2018.